1999
DOI: 10.1037/0097-7403.25.4.491
|View full text |Cite
|
Sign up to set email alerts
|

Drug-onset cues as signals: Intraadministration associations and tolerance.

Abstract: On the basis of a conditioning analysis of drug tolerance, drug-associated cues become associated with the drug effect. These cues elicit conditional compensatory responses and modulate the expression of tolerance. Although there are many findings consistent with the conditioning analysis of tolerance, there also are contrary findings. The results of these experiments suggest that some of the apparently contradictory findings result because interoceptive pharmacological cues, as well as exteroceptive environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(115 citation statements)
references
References 63 publications
6
109
0
Order By: Relevance
“…The method in these experiments consisted of giving a low dose of a drug, paired with a subsequent larger dose of the same drug. These studies have demonstrated acquisition and extinction effects when the low dose of the drug served as the CS (Cepeda-Benito & Short, 1997;Greeley, Lê, Poulos, & Cappell, 1984;Kim, Siegel, & Patenall, 1999;Sokolowska, Siegel, & Kim, 2002). However, these experiments have not compared the relative effectiveness of arbitrary versus drug cues as signals for subsequent drug administration and have not examined such manipulations as blocking, CS-US interval effects, or second-order conditioning.…”
Section: Us-us Versus Cs-us Learningmentioning
confidence: 99%
“…The method in these experiments consisted of giving a low dose of a drug, paired with a subsequent larger dose of the same drug. These studies have demonstrated acquisition and extinction effects when the low dose of the drug served as the CS (Cepeda-Benito & Short, 1997;Greeley, Lê, Poulos, & Cappell, 1984;Kim, Siegel, & Patenall, 1999;Sokolowska, Siegel, & Kim, 2002). However, these experiments have not compared the relative effectiveness of arbitrary versus drug cues as signals for subsequent drug administration and have not examined such manipulations as blocking, CS-US interval effects, or second-order conditioning.…”
Section: Us-us Versus Cs-us Learningmentioning
confidence: 99%
“…In an early demonstration with rats, Greeley et al (1984) found that a low dose of ethanol (0.8 g/kg) reliably paired with a later higher dose of ethanol (2.5 g/kg) came to control an increase in body temperature (i.e., a compensatory hyperthermic CR). For a more recent example, see the research of Siegel and colleagues with morphine (Kim et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although these arguments were developed to account for changes in the analgesic responses to morphine (Daf-f f ters & Bach, 1985;Grisel, Wiertelak, Watkins, & Maier, 1994;Kim et al, 1999;Walter & Riccio, 1983), they may apply to the present results as well. Specifically, morphine was administered subcutaneously in the present studies and is assumed to have a gradual, slow onset of effect, which would overshadow the drug injection cues, subsequently producing the preexposure effect via a pharmacological mechanism (i.e., see Kim et al, 1999;Siegel et al, 2000).…”
Section: Discussionmentioning
confidence: 91%
“…Specifically, morphine was administered subcutaneously in the present studies and is assumed to have a gradual, slow onset of effect, which would overshadow the drug injection cues, subsequently producing the preexposure effect via a pharmacological mechanism (i.e., see Kim et al, 1999;Siegel et al, 2000). If this is the case, degrading the association of the injection cues with morphine's effects by administering extinction injections would not be expected to alter the preexposure effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation